De lo popular a lo masivo: la Revolución mexicana en el cine de la época de oro (1936-1959) - Juan Pablo Silva Escobar (Caravelle)
In this text we maintain that the representations of the Mexican Revolution in the Golden Age movies show a set of rationalities and speeches that legitimize a well-ordered and sanitized view of the revolution. We claim that these narratives contribute to the articulation and strengthening of cultural nationalism, which introduces a myth – in the Barthesian sense of the term – that tends to legitimize a depoliticized discourse about the armed struggle.